The politicization of Mumsnet - Pedersen, Sarah (Bingley, U.K. : Emerald Publishing Limited, 2020)
This book investigates the growing politicization of Mumsnet and its use by politicians to influence middle-class women in the UK. The site's discussion topics go far beyond traditional 'mothering' subjects and encompass politics, feminism and current affairs. Understood as a safe space for gender-critical voices, the site has spawned real-life activism and continues to be both praised and attacked for its support of free speech on controversial subjects. Sarah Pedersen investigates how Mumsnet has become a central part of a resurgent women's rights movement in the UK. She argues that its openness to discussion around this subject has allowed the site to function as a subaltern counter-public - a space where gender-critical feminists have been able to share information and make plans for action and agitation.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: mumsnet.com -- Electronic discussion groups; Women's rights -- Great Britain -- Electronic discussion groups; Electronic discussion groups -- Political aspects -- Great Britain; Parenting -- Great Britain -- Electronic discussion groups; Political Science, Women in Politics; Political activism